1999
DOI: 10.1177/104063879901100411
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Diagnosis of Feline Infectious Peritonitis by Comparison of Protein Content, Cytology, and Direct Immunofluorescence Test on Peritoneal and Pleural Effusions

Abstract: The diagnosis of feline infectious peritonitis (FIP) is hampered by the characteristic etiopathogenesis of the disease. 9 The coronavirus responsible for the disease (FIPV) originated by a mutation in the widespread feline enteric coronavirus (FECV). 9,14 These coronaviruses are both phenotypically and genotypically identical, as demonstrated by polymerase chain reaction (PCR). 14 Both feline coronaviruses (FCoVs) are able to trigger the production of antibodies. High antiFCoV titers are also detectable in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 6 publications
2
57
0
Order By: Relevance
“…A positive result ( Fig. Using direct immunofluorescence to detect FCoV antigens within effusion macrophages, there was a sensitivity of 100% and a specificity of 71.4% (Litster et al, 2013)-results similar to those previously reported (Paltrinieri et al, 1999). Unfortunately, a negative result does eliminate FIP diagnostically because the NPV of 57% is poor (Hartmann et al, 2003;Parodi et al, 1993).…”
Section: Feline Infectious Peritonitissupporting
confidence: 83%
See 2 more Smart Citations
“…A positive result ( Fig. Using direct immunofluorescence to detect FCoV antigens within effusion macrophages, there was a sensitivity of 100% and a specificity of 71.4% (Litster et al, 2013)-results similar to those previously reported (Paltrinieri et al, 1999). Unfortunately, a negative result does eliminate FIP diagnostically because the NPV of 57% is poor (Hartmann et al, 2003;Parodi et al, 1993).…”
Section: Feline Infectious Peritonitissupporting
confidence: 83%
“…Classification as an inflammatory effusion is based primarily on the presence of high total protein (often greater than 4.5 g/dL), which is a reflection of a similar elevation in serum protein, as well as the product of vasculitis and increased vascular permeability. 6-14B) (Norris et al, 2005;Paltrinieri et al, 1999). In a majority of cases the predominant cell is the nondegenerate neutrophil (Fig.…”
Section: Feline Infectious Peritonitismentioning
confidence: 95%
See 1 more Smart Citation
“…This electrophoretic pattern is also evident in effusions when present (Shelly and others 1988, Paltrinieri and others 1998). The macroscopic, physico‐chemical and cytological pattern of the effusion is also typical and has a high positive predictive value for FIP (Paltrinieri and others 1999). It is described as a yellowish, transparent to cloudy, sticky fluid, often with fibrin clots and characterised by high protein content, high specific gravity and variable amounts of cells, mostly composed of non‐degenerated neutrophils, macrophages and lymphocytes in a granular proteinaceous eosinophilic background.…”
Section: Introductionmentioning
confidence: 99%
“…FIPV-infected cells are detected in the pyogranulomas and, based on morphology and the granulocyte/ monocyte/macrophage marker calprotectin, defined as macrophages (Weiss and Scott, 1981;Kipar et al, 1998). Infected mononuclear cells were also isolated from exudates (Cammarata Parodi et al, 1993;Paltrinieri et al, 1999). In one way or another, these infected cells succeed in staying alive and transmitting www.elsevier.com/locate/vetmic Veterinary Microbiology 121 (2007) [131][132][133][134][135][136][137] virus to new susceptible cells in the presence of a high concentration of antibodies.…”
Section: Introductionmentioning
confidence: 99%